SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Engine Operating Parameters on Space- and Species-Resolved Measurements of Engine-Out Emissions from a Single-Cylinder Spark Ignition Engine

Abstract: The development and validation of detailed simulation models of incylinder combustion, emission formation mechanisms and reaction kinetics in the exhaust system are of crucial importance for the design of future low-emission powertrain concepts. To investigate emission formation mechanisms on one side and to create a solid basis for the validation of simulation methodologies (e.g. 3D-CFD, multidimensional in-cylinder models, etc.) on the other side, specific detailed measurements in the exhaust system are requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The experimental investigations were carried out on two homogeneously operated direct injection spark ignition single-cylinder research engines with a displacement volume in the range of modern passenger car engines. The first research engine features an S/B ratio of S/B = 1.2 as presented in previous publications, 5,[20][21][22][23][24][25] whereas the second research engine features an S/B ratio of S/B = 1.5 with the identical bore. Both research engines feature a modular design, allowing the same pistons and cylinder head to be used in both engine setups.…”
Section: Single-cylinder Research Enginementioning
confidence: 95%
“…The experimental investigations were carried out on two homogeneously operated direct injection spark ignition single-cylinder research engines with a displacement volume in the range of modern passenger car engines. The first research engine features an S/B ratio of S/B = 1.2 as presented in previous publications, 5,[20][21][22][23][24][25] whereas the second research engine features an S/B ratio of S/B = 1.5 with the identical bore. Both research engines feature a modular design, allowing the same pistons and cylinder head to be used in both engine setups.…”
Section: Single-cylinder Research Enginementioning
confidence: 95%
“…The specific experimental setup has already been described in other publications from the authors. 7,59,60 The main technical data of the SCE are listed in Table 1.…”
Section: Measurements At the Si DI Research Scementioning
confidence: 99%
“…In this specific measurement campaign, multiple emission measurement devices for gaseous emissions have been applied in different positions, as reported in Esposito et al 59,60 Relevant for this study are the average gaseous emission measurement performed with conventional emission analyzers. These standard measurements have been performed with a FEV Emission Rate (FEVER) device.…”
Section: Measurements At the Si DI Research Scementioning
confidence: 99%
“…In this study, the measurement data came from a specific experimental setup, which was already presented by the authors in [18,19]. The main specifications of the single-cylinder engine are reported in Table 1.…”
Section: Enginementioning
confidence: 99%
“…Additionally, validation requires a comparison in the location where the emission measurements are performed. It was shown in previous works [18,19] that the emission measuring position has a strong impact on the average emission level and cycle-resolved trends. However, validation studies reported in the literature rarely provide details on how the computed emissions were evaluated when compared to experiments.…”
Section: Introductionmentioning
confidence: 98%